Pengaruh Faktor Air Semen terhadap Kuat Tekan Beton dengan Agregat Batu Apung - Pujiono, Agus; Riyanto, Dwi; Pujianto, Asat; Soebandono, Bagus (Semesta Teknika, 2013)
Lightweight concrete is concrete that has a unit weight less than 1800 kg/m3. Pumice can be used to make lightweight concrete as the replacement of coarse aggregate in concrete mixtures. This research aimed to discover the compressive strength of lightweight concrete with water-cement ratio and the impact of the unit weight of the concrete. This research was divided into two types of method. Firstly, the concrete was produced with the water-cement ratio of 0.30, 0.32, 0.34, and 0.36 and additional superplasticiser 2% for each variation. Secondly, the concrete was created with water-cement ratio 0.36, 0.38, 0.40 and 0.42 without admixture. Samples were tested for compressive strength after 28 days and calculated the unit weight of the concrete with pumice as the replacement of coarse aggregate. The results of this study indicated that for the first method, the maximum compressive strength value of lightweight concrete with pumice and additional superplasticiser was 11.2880 MPa with water-cement factor 0.30 and unit weight 1691.59 kg/m3. While for the second experiment, results show that the maximum compressive strength of lightweight concrete with pumice without admixture reached at 10.4620 MPa with a water-cement ratio at 0.38 and unit weight 1692.74 kg/m3.